2017
DOI: 10.1158/1078-0432.ccr-17-0177
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Therapeutic Potential of SOX9 in Chordoma

Abstract: Purpose Conventional chemotherapeutic agents are ineffective in the treatment of chordoma. We investigated the functional roles and therapeutic relevance of the sex-determining region Y (SRY)-box 9 (SOX9) in chordoma. Experimental Design SOX9 expression was examined by immunohistochemistry (IHC) using 50 chordoma tissue samples. SOX9 expression in chordoma cell lines was examined by Western blot and immunofluorescence assays. We used synthetic human SOX9 siRNA to inhibit the expression of SOX9. Cell prolifer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 54 publications
1
27
0
1
Order By: Relevance
“…The physiological functions of SOX9 include cartilage formation, sex differentiation decision, nerve glial and heart development . In addition, it was found that the abnormal expression was related to many human disease and especially in tumours formation and development . SOX9 is over‐expressed in various cancers, such as colorectal cancer, prostate cancer, pancreatic cancer, lung cancer, brain cancer, and melanoma …”
Section: Introductionmentioning
confidence: 99%
“…The physiological functions of SOX9 include cartilage formation, sex differentiation decision, nerve glial and heart development . In addition, it was found that the abnormal expression was related to many human disease and especially in tumours formation and development . SOX9 is over‐expressed in various cancers, such as colorectal cancer, prostate cancer, pancreatic cancer, lung cancer, brain cancer, and melanoma …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, inhibited tumor growth and invasion by SOX9 knockdown shed light on regarding SOX9 as a therapeutic target for cancer. A plenty of studies investigated the correlation between SOX9 expression and prognosis in cancer patients, and demonstrated that upregulated expression of SOX9 in malignant tumors was correlated with poor prognosis in patients with different types of solid tumors such as chordoma [ 13 ], osteosarcoma [ 14 16 ], colorectal carcinoma [ 17 , 18 ], esophageal squamous cell carcinoma [ 10 , 19 ], breast cancer [ 20 23 ], hepatocellular carcinoma (HCC) [ 24 , 25 ], glioma [ 26 ], chondrosarcoma [ 27 ], gastric cancer [ 28 30 ], melanoma [ 31 ], pancreatic ductal adenocarcinoma (PDAC) [ 32 ], ovarian cancer (OC) [ 33 ], prostate cancer [ 34 , 35 ] and non-small cell lung cancer (NSCLC) [ 36 ]. However, some other studies revealed that overexpression of SOX9 was not significantly associated with prognosis of some patients with gastric cancer [ 9 ] and with breast cancer when looking at overall or 5-year survival [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were shown by Chen et al in chordoma cells, a rare type of sarcoma that occurs in the bones of the skull base and spine. They reported that a transient siRNA-based SOX9 knockdown in a chordoma cell line leads to enhanced apoptotic activity [ 30 ]. In line with their data, we observed, a reduction of survivin in the SOX9 knockout clones, but not in the SOX9 knockdown cells.…”
Section: Discussionmentioning
confidence: 99%